Ruang Sehati: Innovating Portable Lactation Pods for Wellness Tourism Using Design Thinking Method in Yogyakarta - Okinarum, Giyawati Yulilania; Vidayanti, Venny; Mulyani, Sri Hasta (Global Medical & Health Communication (GMHC), 2024)
Yogyakarta, a renowned tourist city in Indonesia, currently needs more lactation rooms and public facilities within tourist areas. To address this, inventors propose a portable lactation pod. This study utilized the design thinking method, emphasizing user needs. Interviews were conducted with thirty breastfeeding mothers on Malioboro Street in Yogyakarta to assess the necessity of lactation rooms in this popular tourist spot. From February to June 2022, the stages of "empathize," "define," "ideate," "prototype," and "test" were completed. The findings indicate that the "SEHATI" portable lactation room innovation meets user requirements, with feature satisfaction scores ranging from 4.2 to 4.9 out of 5.0. However, improvements are needed in the ventilation, exhaust fan, and fan sections, which received lower satisfaction scores during the "testing" stage. This innovation could serve as a pilot project, showcasing wellness tourism in Yogyakarta nationally.